Implementation of a process management model and inventory control to increase the level of service in the after-sales area of industrial equipment - Guzman, Pamela (2019)
Currently, many industrial companies generate many losses in their after sales this is generated to an error in the control of inventories and in turn in a mishandling of their assets through their processes, therefore the present research proposes a management model of processes and control of inventories in order to reduce customer losses due to the large number of existing complaints and thus increase sales. Therefore, the process management model, which will contribute to the standardization, optimization and control of its critical processes, and for which indicators, procedures and policies will be proposed for each stage of the process in order to measure its efficiency and effectiveness for correct decision making. With respect to the control of inventories, it is proposed to make a segmentation of the products, which allows the identification of the most important products for the company, to then design a demand forecast model for families of products that will later be individualized considering their factors initial and finally using an inventory management model will obtain the optimal quantity of spare parts order to use in the technical service of the equipment reducing the annual costs related to the inventory.